Growth and yield performance of strawberry (Fragaria ananassa) under various doses of vermicompost and NPK fertilizers grown at rooftop of Charfasson area in the southern parts of Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
A pot experiment was carried out on the rooftop of a building at Charfasson town Bhola to evaluate the growth and yield performance of strawberry (Fragaria ananassa) as influenced by different doses of vermicompost and inorganic fertilizers in the winter season of 2020-2021. Each pot was filled with ten kg soil and arranged in a completely randomized design having seven treatments with three replications. Treatments were T1: Control (-VC), T2: 5 t VC/ha, T3: 10 t VC/ha, T4: 15 t VC/ha, T5: 20 t VC/ha, T6: 25 t VC/ha, and T7: 50% RDF NPK (40 - 15-25 kg/ha). Different agronomic parameters were measured at the intervals of 30, 60, 90, and 120 days after sowing of seeds. All the treatments of vermicompost showed better responses in agronomic parameters than the control treatment. Among them, T5 treatment tends to show significantly (p